ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH JASA PERBANKAN DI PT BANK MUAMALAT INDONESIA TBK,UNIT PELAYANAN SYARIAH TEGAL - Sujarwo, Makmur (PERMANA, 2015)
The purpose of this research is to test the influences of attitude, motivation and religiousness on customer decision.The samples size of this research is 105 customer of Bank Muamalat Tegal. Respondentâs answer for close questions about variable that is researched in this research will be analyzed using index value and Double Regression Examination while the answer for open question will be analyzed qualitative.The results analyze shows that the attitude, motivation and religiousness have positive influence and significant for customer decision.Keywords : attitude, motivation, religiousness and customer decision.